1999
DOI: 10.1016/s0925-4773(99)00177-x
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-calcium exchanger is initially expressed in a heart-restricted pattern within the early mouse embryo

Abstract: Although the sodium-calcium exchanger (NCX1) is encoded by a single gene, it is widely expressed in both fetal and adult tissues and functions in many diverse physiological processes to maintain intracellular calcium homeostasis. In order to determine whether NCX1 is also ubiquitously expressed in the early mouse embryo, in situ hybridization and RT-PCR were used to determine the spacio-temporal expression of NCX1. Our results indicate that NCX1 expression is present within the 7.75-8.0 dpc cardiogenic plate b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 12 publications
3
33
0
2
Order By: Relevance
“…We interpret our results to indicate that the primary purpose of local Ca 2ϩ elevations during diastolic depolarization before an AP is to activate the Na ϩ ͞Ca 2ϩ exchanger, a protein expressed abundantly in early rodent heart and early ES cellderived cardiomyocytes (27,28). The increased inward Na ϩ ͞ Ca 2ϩ exchanger current would accelerate the rate of spontaneous membrane depolarization before an AP (2).…”
Section: Discussionmentioning
confidence: 94%
“…We interpret our results to indicate that the primary purpose of local Ca 2ϩ elevations during diastolic depolarization before an AP is to activate the Na ϩ ͞Ca 2ϩ exchanger, a protein expressed abundantly in early rodent heart and early ES cellderived cardiomyocytes (27,28). The increased inward Na ϩ ͞ Ca 2ϩ exchanger current would accelerate the rate of spontaneous membrane depolarization before an AP (2).…”
Section: Discussionmentioning
confidence: 94%
“…1H). Interestingly, the combined expression patterns of zebrafish NCX1n and NCX1h are comparable to the expression pattern of mammalian NCX1 (23), suggesting that each of these paralogues assumes part of the function of the ancestral NCX1 by subfunctionalization of duplicated genes (22). The distinct expression patterns of NCX1n and NCX1h also suggest that they are involved in different biological processes and that NCX1h has a role in embryonic heart development.…”
Section: Resultsmentioning
confidence: 99%
“…Third, in accordance with this result, NCX1 expression was detected in the WT yolk sac and whole embryo. Although NCX1 transcript in the yolk sac was relatively small amount, it was unexpected because Koushik et al reported that NCX1 was expressed in a cardiacspecific pattern within the early mouse embryo until ED 11.0 (Koushik et al, 1999). Wakimoto et al (2001) also reported that alternatively spliced isoforms of NCX1 were expressed in the whole embryo, as well as in the heart of ED 10.5 mice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Koshik et al showed cardiac restricted NCX1 expression at ED 11.0 using in situ hybridization (Koushik et al, 2001). However, they detected NCX1 in whole embryo at ED 11.0 by PCR analysis (Koushik et al, 1999). Detection by in situ hybridization likely requires that the level of target mRNA within the cell surpasses a concentration threshold (Schneider et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation